Correlation between Spiritual Aspect and Serum Interleukin-6Level in Chronic Hemodialysis Patients - Hanida, Wika; Mudjaddid, E; Nasution, Habibah Hanum; Shatri, Hamzah (Jurnal Penyakit Dalam Indonesia, 2016)
Introduction. Holistic approach in psychosomatic focus on spirituality factor and spiritual support is expected to improve services and psychological condition of the patients. Inflammatory response during hemodialisis procedure hence increased with the evidence of increasing level of serum interleukin-6 (IL-6). Further research is still needed to see the spiritual factors that can decrease the inflammatory factors. Methods. Cross sectional study on 51 chronic hemodialisis patients at RSUP. H. Adam Malik and RSU dr. Pirngadi Medan between July-August 2014. Serum IL-6 was measured using quantitative enzyme-linked immune sorbent assay (ELISA) methods. Blood samples and spiritual aspect assessment by handing out FACIT Sp-12 questionnaire to patients were taken in the morning, 30 minutes before hemodialisis. Results. Subscale meaning 10.67 (SB 2.66), peace 9.63 (SB 2.19) and faith 11.47 (SB 2.91). Median serum IL-6 level is 5,63 (1,48- 28,88) pg/mL. Median FACIT Sp-12 is 30,00 (18-48). Correlation test between serum IL-6 level and spiritual aspect have shown statistically weak negative correlation (correlation coefficient -0,330, p=0.018). Conclusions: spirituality level in chronic hemodialisis patients are higher. Weak negative correlation between serum IL-6 level and spiritual level on chronic hemodialisis patients was found in this study.